Challenges and factors causing difficulties in mastering writing skills: A case study of Indonesian students with mental disability - Ahsin, Muhammad Noor; Darmuki, Agus; Nindyasari, Ratih (Research Journal in Advanced Humanities, 2025)
This study aimed to describe the challenges and factors causing difficulties in learning to write for students with mental disability at Special Needs Senior High School in Indonesia. It was focused on Inclusive School at Kudus Regency, Central Java, Indonesia. It involved students with mental disability. The subjects were taken using purposive sampling. This study involved 40 students and 4 teachers. Data was obtained using observations, interviews, concentrated discussions, documentations, and questionnaires. Result of study showed that students’ challenges in learning to write Indonesian language were (a) having difficulties to write structurally correct sentences; (b) their hand-writing was unclear and illegible; (c) having difficulties to master vocabulary; (d) having difficulties to understand punctuations, and (e) having difficulties in writing correct spelling and grammar. The factors causing those difficulties were (a) students were lack of concentration in learning to write; (b) they had less exercise in writing; (c) limited learning sources; (d) there was no textbook from the government; (e) they had limitations and low abilities; (f) they forgot the learning easily; and (g) there was less interaction and communication in the learning process.